1993
DOI: 10.1017/s0950268800050767
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of oocysts ofCryptosporidiumsp. inLarusspp. gulls

Abstract: SUMMARYBetween November 1990 and February 1991 101 gull faecal samples, collected in central Scotland, and 50 cloacal lavages, from gulls captured at two refuse tips near Durham, England were examined for the presence of Cryptosporidium sp. oocysts. Five of 101 (c 5%) of faecal samples and 11 of 50 (22%) of cloacal lavages contained oocysts, of which 64 % and 83 %, respectively were considered viable when examined with propidium iodide and 4'-6-diamidino-2-phenylindole. Since

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Cryptosporidium was not detected in the wild felids and gulls tested during our study. These low prevalences were consistent with previous studies in which low Cryptosporidium prevalences were reported for bobcats (7%) (82) and gulls (0 to 5%) (46,60). In contrast, Cryptosporidium prevalences of 11% were reported in opossums (24), whereas during our study, detection was greatest in opossums (25%).…”
Section: Discussionsupporting
confidence: 92%
“…Cryptosporidium was not detected in the wild felids and gulls tested during our study. These low prevalences were consistent with previous studies in which low Cryptosporidium prevalences were reported for bobcats (7%) (82) and gulls (0 to 5%) (46,60). In contrast, Cryptosporidium prevalences of 11% were reported in opossums (24), whereas during our study, detection was greatest in opossums (25%).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of cryptosporidiosis and the number of C. parvum-like oocysts in the feces of some wild bird species can be high (14,33). Our findings indicate that birds may serve not only as passive carriers, as suggested by others (11,13), but also as active vectors that increase contamination of water with some C. parvum-like parasites and play a role in waterborne cryptosporidiosis outbreaks.…”
Section: Resultssupporting
confidence: 63%
“…Cryptosporidium oocysts were found in feces and cloacal samples of migratory gulls in Scotland (L. argentatus, L. ridibundus;Smith et al, 1993) and Czechland (L. ridibundus;Pavlásek, 1993). Infectious cryptosporidial oocysts were found in feces of migratory B. canadensis in Maryland (USA; Graczyk et al, 1998).…”
Section: Eimeriinamentioning
confidence: 99%